Ukraine at the Crossroads
XVI, 437 p. 15 illus.
Keywords: "There is no alternative to reforming the Ukranian economy. The benefit of this research is that it makes it possible to view the situation in Ukraine from the outside and to correct reforms in time." Serhiy Tihipko, Vice-Prime Minister of Ukraine "This book, compiled by the German Advisory Group with the Ukranian Government, is testimony to close German-Ukranian cooperation. In supporting this advisory project within the framework of its TRANSFORM programme, the German Federal Government is making an important contribution to the transformation to a social market economy in Ukraine." Walter Kittel, Former State Secretary, Commissioner of the Federal Government of Germany for Technical Cooperation with Central and Eastern Europe "Transition to most economists means Russian collapse or success in Poland or Hungary. Ukraine is by and large ignored even though the country's experience is dramatic. This excellent book documents the tough reform battle. "This country is different" has always been the first step to bad analysis. This book rightly insists on viewing Ukraine's experience in an international perspective. It is not only the only serious source, it is an outstanding one." Rudi Dornbusch, Ford Professor of Economics and International Management, MIT "The analysis and solutions presented in these papers show an immense depth of understanding and originality." Charles Clover, Financial Times.